2019
DOI: 10.3389/fphys.2019.01085
|View full text |Cite
|
Sign up to set email alerts
|

Irisin Exerts Inhibitory Effect on Adipogenesis Through Regulation of Wnt Signaling

Abstract: Irisin is an exercise-induced myokine known to induce adipocyte browning through induction of uncoupling protein 1. Recent studies have reported that irisin is also an adipokine. However, there is limiting evidence on the role of endogenous irisin from adipocytes. In this study we aim to elucidate the expression and secretion pattern of irisin during adipocyte differentiation and the role of endogenous and exogenous irisin on the adipogenic process. As such, recombinant irisin, plasmid expressing FNDC5 and sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 47 publications
0
27
0
1
Order By: Relevance
“…Therefore, besides of the main role of irisin which is browning of WAT, irisin also prohibits accumulation of lipids through up-regulation of adipose triglyceride lipase (ATGL) and down regulation of fatty acid synthase (FAS) [41]. This modulatory effect is mediated by the PPARγ, C/EBPa, and FABP4 axis under control of Wnt signaling, as FNDC5/irisin up regulates Wnt6 and Wnt10a and Wnt 10b [42]. Wnt signaling is inhibitory for adipocyte differentiation [43].…”
Section: Adipogenesis Is Suppressed By Irisin Through Wnt Signalingmentioning
confidence: 99%
“…Therefore, besides of the main role of irisin which is browning of WAT, irisin also prohibits accumulation of lipids through up-regulation of adipose triglyceride lipase (ATGL) and down regulation of fatty acid synthase (FAS) [41]. This modulatory effect is mediated by the PPARγ, C/EBPa, and FABP4 axis under control of Wnt signaling, as FNDC5/irisin up regulates Wnt6 and Wnt10a and Wnt 10b [42]. Wnt signaling is inhibitory for adipocyte differentiation [43].…”
Section: Adipogenesis Is Suppressed By Irisin Through Wnt Signalingmentioning
confidence: 99%
“…To investigate the mechanism underlying how r-irisin increased osteoblast differentiation, we analyzed signaling pathways which irisin regulated based on reported studies, and found that irisin could modulate Notch [43], focal adhesion kinase (FAK) -extracellular signal-regulated kinase (Erk) -mitogen-activated protein (MAP) [23,25,44,45], reactive oxygen species (ROS) [46,47], phosphatidylinositol-3-kinase (PI3K) -v-akt murine thymoma viral oncogene homolog 1(AKT) [48], and Wnt/β-catenin [27,37,45] signaling pathways. Significantly, it is reported that irisin inhibited adipogenesis through regulating the Wnt/β-catenin signaling pathway [37]. In addition, Wnt antagonists sclerostin and dickkopf-1 were downregulated in MLO-Y4 cells after treatment with r-irisin [45].…”
Section: Discussionmentioning
confidence: 99%
“…Irisin was reported to exert inhibitory effect on adipogenesis through regulating the Wnt/β-catenin signaling pathway [37], which is a key signaling pathway in controlling osteoblast differentiation and bone formation [38]. Colaianni et al demonstrated that r-irisin could increase β-catenin expression during differentiation of bone marrow stromal cells [27].…”
Section: R-irisin Promotes β-Catenin Expression To Regulate Osteoblasmentioning
confidence: 99%
See 1 more Smart Citation
“…Irisin is a recently identified myokine, which is mainly expressed and secreted by skeletal muscles as a cleavage product of fibronectin type III domain containing 5 (FNDC5) [ 14 ]. Furthermore, irisin is produced by adipose tissue; therefore, it seems to function as a myokine as well as an adipokine [ 15 , 16 , 17 ]. The regulation of irisin levels is dependent on PPAR-γ (peroxisome proliferator-activated receptor gamma) coactivator-1-α (PGC1α).…”
Section: Introductionmentioning
confidence: 99%